Kingdom of the Netherlands-Curacao and Sint Maarten : 2021 Article IV Consultation Discussions; Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The COVID-19 pandemic inflicted another major shock on the economies of Curacao and Sint Maarten, which followed category 5 hurricanes in Sint Maarten in 2017 and the spillovers of the Venezuelan crisis on Curacao. Despite the substantial response measures financed by The Netherlands, the economic contraction in 2020 was severe.